b - Wegela, Karen Kissel (b, 2009)
The quality of presence a psychotherapist or counselor brings to the therapeutic relationship makes all the difference in effective treatment. With this application of Buddhist practice to psychotherapy, Karen Kissel Wegela offers mental health professionals a new perspective on bringing compassion, patience, generosity, and equanimity to their work with clients. She also shows how counselors can apply this wisdom in their own lives, and how they can help their clients to cultivate these qualities in themselves.
Includes bibliographical references and index.
Keywords: v; Buddhism -- Doctrines; Meditation -- Buddhism